Highly sensitive and stable electrochemical sulfite biosensor incorporating a bacterial sulfite dehydrogenase. - Kalimuthu, P; Tkac, J; Kappler, U; Davis, J; Bernhardt, P (2010)
This paper describes a highly sensitive electrochemical (voltammetric) determination of sulfite using a combination of Starkeya novella sulfite dehydrogenase (SDH), horse heart cytochrome c (cyt c), and a self-assembled monolayer of 11-mercaptoundecanol (MU) cast on a gold electrode. The biosensor was optimized in terms of pH and the ratio of cyt c/SDH. The electrocatalytic oxidation current of sulfite increased linearly from 1 to 6 microM at the enzyme-modified electrode with a correlation coefficient of 0.9995 and an apparent Michaelis constant (K(M,app)) of 43 microM. Using an amperometric method, the low detection limit for sulfite at the enzyme-modified electrode was 44 pM (signal-to-noise ratio = 3). The modified electrode retained a stable response for 3 days while losing only ca. 4% of its initial sensitivity during a 2 week storage period in 50 mM Tris buffer solution at 4 degrees C. The enzyme electrode was successfully used for the determination of sulfite in beer and white wine samples. The results of these electrochemical analyses agreed well with an independent spectrophotometric method using Ellman's reagent, but the detection limit was far superior using the electrochemical method.